An Enantioselective Assembly of Dihydropyranones through an NHC/LiCl‐Mediated in situ Activation of α, β‐Unsaturated Carboxylic Acids. Issue 5 (10th February 2016) - Que, Yonglei; Lu, Yinan; Wang, Wenjing; Wang, Yuhong; Wang, Haotian; Yu, Chenxia; Li, Tuanjie; Wang, Xiang‐Shan; Shen, Shide; Yao, Changsheng
Abstract: A straightforward N ‐heterocyclic carbene (NHC)/LiCl‐mediated synthesis of dihydropyranones from α, β‐unsaturated carboxylic acids and 1, 3‐dicarbonyl compounds was realized through the in situ activation strategy. The key advantages of this protocol include ready availability and high stability of starting materials, good yields, and excellent enantioselectivity. Abstract : Face like a pyranone : A straightforward N ‐heterocyclic carbene (NHC)/LiCl‐mediated synthesis of dihydropyranones from α, β‐unsaturated carboxylic acids and 1, 3‐dicarbonyl compounds was realized through an in situ activation strategy. The key advantages of this protocol include ready availability and high stability of starting materials, good yields, and excellent enantioselectivity.